THE EFFECT OF PROBLEM-BASED LEARNING TO THE SPEAKING ABILITY OF THE TENTH GRADE STUDENTS - Nurhazizah Nurhazizah; Mukrim Mukrim; Muhammad Arid; Nadrun Nadrun (Tadulako University, 2022)
The objective of this research is to find the effect of problem-based learning to the speaking ability of the tenth grade students at SMK Muhammadiyah 1 Palu. This research employed experimental research of quasi-experimental design. The samples were the students of X Farmasi as the experimental group and the students of X TKJ A as the control group. They were selected using convenience sampling technique. The data were collected through pretest and posttest analyzed by using t-test formula to compare the mean score of the experimental and control groups. The result of the data analysis shows that t-table (1.968) higher than t-value (0.96), so the hypothesis is rejected. It means problem-based learning has no effect significantly to the students speaking ability. That caused by several factors such as situation, teaching implementation, and students participation.